Use and perceived usefulness of a just-in-time resonance breathing intervention adjunct for substance use disorder: Contextual and physiological predictors - Price, Julianne L.; Bates, Marsha E.; Pawlak, Anthony P.; Uhouse, Sarah Grace; Todaro, Sabrina M.; Morgano, Julie; Buckman, Jennifer F. (Frontiers in Psychiatry, 2022)
Craving for alcohol and other drugs is often described as a momentary hyperarousal state that interferes with one's ability to use top-down strategies. As such, it may be best interrupted ‘in the moment' through bottom-up modulation. We recently reported that episodic resonance paced breathing (eRPB) delivered via mobile phone app as an add-on to outpatient treatment for substance use disorder (SUD) was effective at dampening craving over the course of an 8-week intervention (NCT#02579317). However, not all participants engaged with the eRPB app and there was high intra- and inter-individual variability in weekly ratings of usefulness. Here we examined baseline demographic, physiological, and psychiatric measures as well as time-varying exposure to positive, negative, and temptation craving triggers as predictors of frequency of eRPB app use and ratings of usefulness. Seventy-seven outpatient women were randomized to an eRPB (0.1 Hz) or a faster paced breathing sham (0.23 Hz) condition. Baseline measures were assessed within the first 3 weeks of treatment entry prior to randomization. App use frequency, ratings of usefulness, and trigger exposure were measured weekly throughout the intervention. Variables were entered into marginal means models with forward stepwise model selection and examined as predictors of use and usefulness. Frequent app use was associated with a lifetime alcohol use disorder (AUD) diagnosis (p = 0.026), higher ratings of usefulness (p < 0.001), and fewer exposures to positive triggers (e.g., celebration, socialization; p < 0.001). There was a trend-level association between frequency of app use and greater cardiovascular capacity at baseline (p = 0.088). Higher ratings of usefulness were associated with greater exposure to negative triggers (e.g,. loneliness, frustration; p < 0.001) and parasympathetic dysregulation at baseline (p = 0.05). A positive relationship between app use frequency and ratings of usefulness was present only in the eRPB group (p = 0.045). Matching ideal candidates and moments to an arousal modulation anti-craving intervention can help streamline screening and implementation of eRPB in the treatment of SUD. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT02579317, identifier NCT02579317.